(untitled) (Raparin Journal of Humanities (RJH), 2024)
This research is a scientific attempt to find out the relationship between journalists’ skills and social network management in the Kurdistan Region, where Facebook is taken as an example of social networks, as well as determine the level of skills of the journalist in digital media related to each area; (production and editing of text, information technology, technique, working in social networks). This research is a causal research conducted by descriptive method and survey method and the researcher relied on survey form tool to obtain information. According to the researcher’s observations of Kurdish media outlets in the Kurdistan Region, the number of journalists involved in managing their Facebook pages is 500, of which the researcher sampled 145 journalists, which is 29 percent of the journalists involved in managing Facebook pages. In this research, the researcher concluded that there is a strong direct statistical relationship between (journalists’ skill level and social network management). In general, with increasing skill level, journalists can better manage social networks, including Facebook. In order to be successful in working on social networks, a journalist needs a number of skills, the most important of which are; Adapting to the nature of the network, interacting with the recipient, analyzing social network statistics, and account safety.